2020
DOI: 10.1017/ice.2020.367
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve antibiotic prescribing at hospital discharge: A systematic review

Abstract: A large proportion of antibiotic use associated with hospitalization occurs immediately after discharge, representing an important focus for antimicrobial stewardship programs. This review identified few studies evaluating the effect of interventions aimed at improving discharge antibiotic prescribing. Antimicrobial stewardship to improve postdischarge antibiotic prescribing is an unmet need warranting further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Some of the proposed models include developing an institutional guidance for oral step-down antibiotic and duration, pharmacy-led discharge review, providing discharge advice as part of routine ASP interventions, and incorporating antibiotic timeout at discharge. 9,10 The limitation of our study is its small sample size in a single center, which limits its generalizability. The retrospective nature of this study may have impeded the accuracy of our assessment.…”
Section: Discussionmentioning
confidence: 97%
“…Some of the proposed models include developing an institutional guidance for oral step-down antibiotic and duration, pharmacy-led discharge review, providing discharge advice as part of routine ASP interventions, and incorporating antibiotic timeout at discharge. 9,10 The limitation of our study is its small sample size in a single center, which limits its generalizability. The retrospective nature of this study may have impeded the accuracy of our assessment.…”
Section: Discussionmentioning
confidence: 97%
“…Few studies have described AS efforts at discharge and their impact on antimicrobial prescribing. [15][16][17][18][19] Most studies focus on antimicrobial appropriateness before and after AS intervention, although intervention strategies vary between studies. Yogo et al performed a quasi-experimental, retrospective cohort study that used an institutional guideline with recommendations for oral step-down therapy and treatment duration in conjunction with prospective audit with real-time feedback to prescribers.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Daniels and Weber performed a systematic review assessing interventions to improve antimicrobial prescribing at hospital discharge. 19 However, only a few studies were identified for inclusion (n = 6). The authors concluded that AS interventions focused on improving discharge antimicrobial prescribing need further study.…”
Section: Discussionmentioning
confidence: 99%
“…There is a particular focus on antimicrobial stewardship, which refers to the efforts made to ensure that antimicrobials are used only when necessary and appropriate. It was first established as a set of “responsible use” policy measures to combat AMR in human hospitals ( 35 ) and is now used widely in human medicine ( 36 , 37 ). In food animal production, antimicrobial stewardship similarly refers to a commitment to judicious use of antimicrobials ( 38 – 40 ), including efforts to limit inappropriate usage, to optimise the choice, dose rate, route, and duration of therapy to maximise clinical cures, and to minimise the emergence and spread of AMR.…”
Section: The Evidence Consideredmentioning
confidence: 99%